2023
DOI: 10.1055/a-2006-1018
|View full text |Cite
|
Sign up to set email alerts
|

Rare Diseases in Hospital Information Systems—An Interoperable Methodology for Distributed Data Quality Assessments

Abstract: Background: Multisite research networks such as the project “Collaboration on Rare Diseases” connect various hospitals to obtain sufficient data for clinical research. However, data quality (DQ) remains a challenge for the secondary use of data recorded in different health information systems. High levels of DQ as well as appropriate quality assessment methods are needed to support the reuse of such distributed data. Objectives: The aim of this work is the development of an interoperable methodology for assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…9 With “consistency comprises indicators that use Boolean type checks to identify inadmissible, impossible, or uncertain data values or combinations of data values,” Yusuf et al cite an orthogonal perspective on this dimension. 11 Tahar et al decline the use of the term “consistency” for their study and refer to plausibility instead, broadly defined as “deviations from expected values.” 14 Smith et al talk about “consistency and similarity of synthetic samples” without precisely mentioning their interpretation of the dimension. 16 Beyond the different interpretations of terms that are directly related to the topic data quality, one might imagine similar deviations regarding basic concepts such as “data set” or “metadata.” Tahar et al looked at those terms and propose respective definitions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…9 With “consistency comprises indicators that use Boolean type checks to identify inadmissible, impossible, or uncertain data values or combinations of data values,” Yusuf et al cite an orthogonal perspective on this dimension. 11 Tahar et al decline the use of the term “consistency” for their study and refer to plausibility instead, broadly defined as “deviations from expected values.” 14 Smith et al talk about “consistency and similarity of synthetic samples” without precisely mentioning their interpretation of the dimension. 16 Beyond the different interpretations of terms that are directly related to the topic data quality, one might imagine similar deviations regarding basic concepts such as “data set” or “metadata.” Tahar et al looked at those terms and propose respective definitions.…”
Section: Discussionmentioning
confidence: 99%
“…using synthetic data. 14 As a unique contribution to this focus theme, the authors provide definitions of basic concepts as "data item" carefully distinguishing between the levels of data and metadata. The authors demonstrated the applicability of their approach interconnecting three university hospitals with a Personal Health Train.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations